Measuring divergence/convergence within the Economic and Monetary Union - Guerreiro, Pedro Gustavo Campaniço da Palma (2016)
The Economic and Monetary Union was an advance stage towards a complete integration across European countries. We are interested in understand to what extent the common currency has contributed to strengthen the co-movement between Euro area countries. Ehrmann et al.(2011) study convergence by looking at the sovereign bond markets. The authors consider the four Eurozone largest economies, for three different maturities and using high-frequency data. This dissertation extends their research through an updated dataset. As expected we obtain the exact same results for the period we have in common - strong convergence with Euro’s introduction. After 2008, the picture changes dramatically. We see a great divergence, which seems to be triggered during the European sovereign debt crisis. This path is reversed in the last part of our dataset, however, the market integration never return to the level experienced during the first nine years of EMU. We innovate this field of analyses through the introduction of a univariate analyses. We conclude that the convergence patterns detected in the zero-coupon yields are to a large extent structural. The great divergence observed after the crisis gave rise to a striking tendency - the formation of two country blocks within the EMU. We discuss possible reasons behind the convergence dynamics observed in the sovereign bond markets and, future implications for the European complete integration goal.